Randomized control comparative study to evaluate the effect of camylofin dihydrochloride and valethamate bromide in active phase of first stage of labour - Agarwal, Shonali N.; Shah, Vidhi H.; Gokhale, Ashish V.; Amin, Juhi V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Numerous drugs have been used to shorten the active phase of labor. Do they really shorten the duration of labor? What adverse effects do they have on the baby and the mother? These questions were the basis to perform the present study of comparing two of such drugs, injection Camylofin dihydrochloride and injection Valethamate bromide with control subjects. Aim of the study was to assess the effect of camylofin dihydrochloride and valethamate bromide on active phase of first stage of labour. Methods: This is an open label randomized controlled study of 120 eligible women with spontaneous onset of labour at SSG hospital, Vadodara, India. Women were randomized to receive either a single intra-muscular Camylofin, 3 doses of intra-venous Valethamate or third as control group. The main outcome measure was duration of active phase of first stage of labour and rate of cervical dilatation. The study was conducted over a period of 9 months from May 2022 to January 2024. Results: Mean duration of active phase of labour was 4.33±1.32 hours, 6.74±1.26 hours and 6.83±1.65 hours in Camylofin, Valethamate and control group respectively with p value <0.0001. Mean rate of cervical dilatation was 1.47±0.41 cm/hour, 0.91±0.23 cm/hour and 0.87±0.18 cm/hour in three groups respectively. There was no significant difference in maternal side effects and neonatal outcome among them. Conclusions: Considering the results of this study, it can be concluded Camylofin is superior to Valethamate in decreasing total duration of active phase of first stage with higher cervical dilatation rate.